Observations of polycyclic aromatic hydrocarbons at Changbai Mountain in Northeast Asia: Characteristics, transboundary transport, and health impacts - Ye Shan; Yifan Li; Lanxin Zhang; An’an Qi; Yujiao Zhu; Yanbin Qi; Lingxiao Yang; Liubin Huang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Lingli Zhang; et al. (Journal of Environmental Sciences, 2026)

Insights into atmospheric trace gases, aerosols, and transport processes at a high-altitude station (2623 m a.s.l.) in Northeast Asia - Ye Shan; Yujiao Zhu; Yanbi Qi; Yu Yang; Jiangshan Mu; Mingxuan Liu; Hongyong Li; Ji Zhang; Yanqiu Nie; Yuhong Liu; Min Zhao; Xin Zhang; et al. (Atmospheric Environment, 2024)

Safety of azithromycin in pediatrics: a systematic review and meta-analysis - Linan Zeng; Peipei Xu; Imti Choonara; Zhenyan Bo; Xiangchen Pan; Wenyan Li; Xiaofeng Ni; Tao Xiong; Can Chen; Leshan Huang; Shamim Ahmad Qazi; Dezhi Mu; et al. (European Journal of Clinical Pharmacology, 2020)
Purpose To evaluate the toxicity of azithromycin in neonates, infants, and children. Methods A systematic review was performed for relevant studies using Medline (Ovid), PubMed, Cochrane Central Register of Controlled Trials, EMBASE, CINAHL, and International Pharmaceutical Abstracts. We calculated the pooled incidence of adverse drug reactions (ADRs) associated with azithromycin based on prospective studies (RCTs and prospective cohort studies) and analyzed the risk difference (RD) of ADRs between azithromycin and placebo or other antibiotics using meta-analysis of RCTs. Results We included 133 studies with 4243 ADRs reported in 197,675 neonates, infants, and children who received azithromycin. The safety of azithromycin as MDA in pediatrics was poorly monitored. The main ADRs were diarrhea and vomiting. In prospective non-MDA studies, the most common toxicity was gastrointestinal ADRs (938/1967; 47.7%). The most serious toxicities were cardiac (prolonged QT or irregular heart beat) and idiopathic hypertrophic pyloric stenosis (IHPS). Compared with placebo, azithromycin did not show increased risk ADRs based on RCTs (risk difference − 0.17 to 0.07). The incidence of QT prolonged was higher in the medium-dosage group (10–30 mg/kg/day) than that of low-dosage group (≤ 10 mg/kg/day) (82.0% vs 1.2%). Conclusion The safety of azithromycin as MDA needs further evaluation. The most common ADRs are diarrhea and vomiting. The risk of the most serious uncommon ADRs (cardiac-prolonged QT and IHPS) is unknown.

Dietary fibres modulate the composition and activity of butyrate-producing bacteria in the large intestine of suckling piglets - Chunlong Mu; Lingli Zhang; Xiangyu He; Hauke Smidt; Weiyun Zhu (Antonie van Leeuwenhoek, 2017)

Global detection of large lunar craters based on the CE-1 digital elevation model - Lei Luo; Lingli Mu; Xinyuan Wang; Chao Li; Wei Ji; Jinjin Zhao; Heng Cai (Frontiers of Earth Science, 2013)

Cratering process and morphological features of the Xiuyan impact crater in Northeast China - XinYuan Wang; Lei Luo; HuaDong Guo; LingLi Mu; Chao Li; Wei Ji; Heng Cai (Science China Earth Sciences, 2013)

Primary scientific results of Chang’E-1 lunar mission - ZiYuan Ouyang; ChunLai Li; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; JianJun Liu; Wei Zuo; Yan Su; WeiBin Wen; Wei Bian; BaoChang Zhao; et al. (Science China Earth Sciences, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

Triaxial ellipsoid models of the Moon based on the laser altimetry data of Chang’E-1 - WenRui Wang; Fei Li; JianJun Liu; Xin Ren; XiaoDuan Zou; LingLi Mu; JianGuo Yan; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)